FOREIGN EXCHANGE RATES IN CENTRAL EUROPEAN ECONOMIES: NONLINEARITIES IN ADJUSTMENT TO INTEREST RATE DIFFERENTIALS - Sznajderska, Anna (Metody Ilościowe w Badaniach Ekonomicznych, 2013)
The aim of the paper is to examine the relation between foreign exchange rates and interest rate differentials in Poland, the Czech Republic, and Hungary. The exchange rate equations are inspired by the uncovered interest rate parity (i.e. the UIP condition). The results of empirical studies are usually contrary to the UIP condition. One of the explanations of this puzzle is the existence of certain nonlinearities. The nonlinearities appear because of transaction costs, central bank interventions, limits of speculations, hysteresis, or changes in risk perception. I estimate smooth transition autoregressive models. The threshold variable is an interest rate differential or a level of economic activity. I examine the exchange rates of USD and EUR and 1-, 3- and 6- months and 5- years interest rates. I also test various proxies for risk premium.